First High‐resolution GPR and Magnetic Archaeological Prospection at the Viking Age Settlement of Birka in Sweden. Issue 3 (4th March 2014) - Trinks, Immo; Neubauer, Wolfgang; Hinterleitner, Alois
ABSTRACT In May 2006 high‐resolution measurements using ground‐penetrating radar (GPR) and magnetic gradiometer systems conducted over selected areas at the site of the Viking Age settlement and trading place Birka in central Sweden demonstrated the suitability of these methods for archaeological prospection of Scandinavian proto‐urban settlements. The non‐invasive geophysical surveys revealed numerous structural details of the settlement: houses, property boundaries, track‐ways, buried remains of the town ramparts dating from different building periods, including a gate, were mapped with a manually operated single‐channel GPR system and a four‐channel magnetometer array. The combination of these two prospection methods, state‐of‐the‐art data processing and visualization and archaeological interpretation within a geographical information system resulted in valuable new information about the UNESCO World Cultural Heritage Site Birka‐Hovgården. We present methodology and results of this first archaeological prospection case study conducted in 2006. Copyright © 2014 John Wiley & Sons, Ltd.